2022
DOI: 10.1101/2022.04.04.22273380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuromodulation through Brain Stimulation-assisted Cognitive Training in Patients with Post-Chemotherapy Cognitive Impairment (Neuromod-PCCI): Study Protocol of a Randomized Controlled Trial

Abstract: IntroductionBreast cancer is the most common form of cancer in women. A considerable number of women with breast cancer who have been treated with chemotherapy, subsequently develop neurological symptoms such as concentration and memory difficulties (also known as ‘chemobrain’). Currently, there are no validated therapeutic approaches available to treat these symptoms. Cognitive training holds the potential to counteract cognitive impairment. Combining cognitive training with concurrent transcranial direct cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…In adult and pediatric cancer populations, transcranial and transcutaneous stimulation studies are limited, but success has been demonstrated. Adult breast cancer survivors who received transcranial stimulation paired with attentional cognitive training demonstrated improved attentional scores and reduced cognitive dysfunction [ 91 , 97 ]. A 2014 case study of a breast cancer survivor with chemo-related cognitive impairment demonstrated the efficacy of DLPFC transcranial stimulation on global cognition, attention, executive function, and memory [ 92 ].…”
Section: Existing Therapeutic Interventions For Cognitive Impairmentmentioning
confidence: 99%
“…In adult and pediatric cancer populations, transcranial and transcutaneous stimulation studies are limited, but success has been demonstrated. Adult breast cancer survivors who received transcranial stimulation paired with attentional cognitive training demonstrated improved attentional scores and reduced cognitive dysfunction [ 91 , 97 ]. A 2014 case study of a breast cancer survivor with chemo-related cognitive impairment demonstrated the efficacy of DLPFC transcranial stimulation on global cognition, attention, executive function, and memory [ 92 ].…”
Section: Existing Therapeutic Interventions For Cognitive Impairmentmentioning
confidence: 99%